Research of catalytic damage of fabric by rust during a cold peroxid bleaching - Кулігін, Михайло Львович; Сарібєкова, Діана Георгієвна (Eastern-European Journal of Enterprise Technologies, 2012)
The bleaching by hydrogen peroxide at low temperatures is widely spread in Ukrainian textile mills. The cold bleaching differs by uniformity and soft effect, which provide preventing of cellulose from destruction. However, in some cases on the works during the bleaching of cotton, small holes appear. There is a supposition that they are the result of catalytic damage of cellulose during the bleaching under the effect of rust that gets on fabrics during impregnation and bleaching solutions production. The target of the research was to study the possibility of catalytic damage of cotton by rust, particles of iron, aluminium and copper during the cold bleaching by hydrogen peroxide. As follows from the results of the research, there is a certain difference in the process of decomposition of hydrogen peroxide by d-metals and rust in liquid medium and process of decomposition on the substrate. In liquid medium the small number of catalysts cause rapid decomposition of hydrogen peroxide even with stabilizer in bleaching solution. It was determined due to the research that rust in the bleaching solution with concentration up to 200 mg/l will not cause deterioration or damage to the fabrics. In addition, even considerable amount of rust will not deteriorate fabrics and will not cause visible damages, holes and burns. Aluminium, copper, iron and corrosionproof iron powders will not deteriorate and damage fabrics.